Oral manifestation of thalassemia ï¢ mayor: case study - Widodo, Haris B.; Maharani, Aisya E. (Journal of Case Reports in Dental Medicine, 2019)
Objective: Thalassemia b major is one of inheredited blood disorder caused by abnormality hemoglobin. Thalassemia b major is widely found in population Mediteranian with prevalent Â±25.000 case. The abnormal form of hemoglobin chain will lead to erythrocytes damage in <120 days and will distrurb osteogenesis process. This condition caused patient with thalassemia b major require blood transfusion. The purpose of this paper is to describe an oral manifestation of thalassemia b major.Methods: the patient (5 years old) came to dental hospital of Jenderal Soedirman University with his mother for having teeth treatment. The patient was diagnosed thalassemia b major since 1 years old of and has had regular blood transfusion every month. An examination of intraoral examination showed pale oral mucose (purplish), profound caries on 85th teeth exposed to pulp, overbite 4mm, overjet 3mm, deep palatum, and the extraoral examination showed special face shape.Results: Clinical examinations performed on patients showed the characteristics of cooley-face and the cephalo-tracing x-ray result, the were <SNA = 86o, <SNB = 81o, <ANB = 5o, and <FH-Man = 35o. Based on the radiographic results it can be seen that patients with thalassemia have skeletal class II tendency and there is more anterior or protusive appearence of maxillary growth.Conclusion: Thalassemia sufferers have oral manifestations which are characterized by Cooley-face. Patients with thalassemia have skeletal class II tendency and there is more anterior or protusive appearence of maxillary growth.Keyword: Hemoglobin, Oral manifestation, Thalassemia b mayor.